Recent Publications (Quarterly Journal of Economics, 1946)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 60, Issue 2, February 1946, Pages 309–312, https://doi.org/10.1093/qje/60.2.309 Published: 01 February 1946